Transmission losses cost allocation in restructed electricity market environment - Jaini, Nur ‘Afiqah (2014)
During these recent decades, the restructuring system of electricity market has been taken places around the whole world. Due to the restructuring (deregulation), the electrical power system has been divided into three separates categories according to the function. First stage of power system is the generation companies (GENCOs), followed by transmission companies (TRANSCOs) and distribution companies (DISCOs). The competitive environment will be handling by a non-profit entity, independent system operator (ISO) that functioning as the system securities that have to make sure that the power system continues to operate in a stable and economical manner. However, restructuring system can give effect during the energy transmission. One of the transmission issues is regarding the power losses. To overcome the losses, generators must generate more power. The issue regarding the transmission losses in deregulated system is how to allocate it to the user and charge them in fair ways as in for instance the pool trading model, it is hard to trace the power contribution and losses of each user in transmission line. In addition, the users didn’t want to pay the losses, it means that the ISO have to responsible for the losses and it will be unfair to put the responsible to ISO alone. Therefore, in this project, the allocation of transmission losses and loss cost methods which are the pro-rata and proportional sharing method will be investigated. Comparison between those methods will be done in order to identify which types of method that reflect an efficient and fair way to distribute the cost of the transmission losses to the user. These chosen methods will be tested on IEEE bus system.